Diagnosis of Heterotaxy Syndrome in a Patient With Multiple Congenital Cardiac Malformations Using Magnetic Resonance Imaging. (September 2020) - Murat, Sani Namik; Yalcinkaya, Damla; Yarlioglues, Mikail; Yigit, Hasan; Bozkurt, Ugur; Celik, Ibrahim Etem; Oksuz, Fatih; Atik, Fatih; Duran, Mustafa
Abstract : Supplemental Digital Content is available in the text.